Parametric investigation and economic design of slender steel fibre reinforced concrete beams using shear resisting mechanisms approach. (December 2022) - Negi, Bichitra Singh; Jain, Kranti; Dighade, R.R.
Abstract: The shear resisting mechanisms (SRM) in slender steel fibre reinforced concrete (SFRC) beam (without stirrups) comprised of four shear resisting mechanisms (uncracked concrete in the compression zone, the dowel action of the longitudinal reinforcement bars, the aggregate interlocking through the aggregates protruding at the critical diagonal shear crack, and the steel fibres bridging the diagonal crack). These shear resisting mechanisms are interrelated to each other and very complex to quantify. However, parametric analysis is one of the methods which can easily be applied and quantify their interconnection. As a result, the parametric analysis has been carried out in this research with the main focus on the effect of influential parameters on shear strength, shear resisting mechanisms, and the interrelationship between them. Thus, the SRM model has been again verified and validated through the results of parametric investigation. Furthermore, the SRM based model has been further modified, and a cost analysis for economic beam design was performed. Finally, design recommendations from the standpoint of practical application have been proposed.